The effectiveness of the Internet-based self-management program for cancer-related fatigue patients: a systematic review and meta-analysis. (March 2020) - Huang, Junting; Han, Yang; Wei, Jiejie; Liu, Xiaobo; Du, Yanying; Yang, Linqing; Li, Ying; Yao, Wanxia; Wang, Ruijun
Objective: To systematically investigate how fatigue, depression, anxiety, sleep quality, and life quality are influenced by the Internet-based self-management program (IBSMP) among cancer patients. Data sources: Eight databases (Cochrane Library, Ovid, Web of Science, Medline, Embase, Chinese biomedical database (CBM), China National Knowledge Infrastructure (CNKI), and Wanfang) were systematically searched from inception to January 2019. Methods: The aim of this study is to identify randomized controlled trials (RCTs) associated with the IBSMP among cancer-related fatigue (CRF) patients. Two reviewers independently screened 1128 records and selected 13 articles, including 1603 patients for inclusion. The quality of the evidence was assessed at the study level and at the outcome level. Results: The meta-analysis showed that the IBSMP was effective for ameliorating fatigue and related symptoms among cancer survivors (the Brief Fatigue Index, relative risk = 0.74, 95% confidence interval (CI; 0.69, 0.79), P < 0.01; the Cancer Fatigue Scale or the Multidimension Fatigue Scale, weighted mean difference = −10.15, 95% CI (−11.42, −8.89), P < 0.01; the Self-rating Anxiety scale, relative risk = 1.07, 95% CI (0.55, 2.05), P < 0.01; the Self-rating Depression scale, relative risk = 0.70, 95% CI (0.60, 0.81), P < 0.01; the Pittsburgh Sleep Quality Index, relative risk = 0.46, 95% CI (0.33, 0.62), P < 0.01; and the Function Assessment of Cancer Therapy—General scale or the Function Assessment of Cancer Therapy—Breast, weighted mean difference = 13.76, 95% CI (3.38, 24.14), P < 0.01.) Conclusion: This meta-analysis demonstrates that the IBSMP, as one of the rehabilitation forms, can reduce the incidence of fatigue, depression, and anxiety and improve sleep quality and life quality among CRF patients.